Establishment of an In-House Indirect Enzyme-Linked Immunosorbent Assay to Detect Antibodies Against African Horse Sickness Based on Monovalent and Polyvalent Live Attenuated Vaccines During the First Outbreak in Thailand - Darsaniya Punyadarsaniya; Machimaporn Taesuji; Khate Rattanamas; Sakchai Ruenphet (Animals)
Standard serological tests post-vaccination, such as enzyme-linked immunosorbent assay (ELISA), complement fixation, and virus neutralization, are crucial for monitoring African horse sickness (AHS). However, the availability of commercial test kits such as blocking ELISA varies by regions; while they are commonly used in Africa and Europe, their limited availability and high cost in Thailand present significant challenges. Therefore, this study aimed to evaluate an alternative approach using an in-house indirect ELISA based on cell-based monovalent and polyvalent strains of live attenuated AHS virus. This method addresses the cost and accessibility issues faced in Thailand. This study demonstrated promising results: the in-house indirect ELISA showed analytical sensitivity and specificity values of 88.30% and 67.02% for monovalent strains and 87.23% and 84.04% for polyvalent strains, respectively, compared to the blocking ELISA. These findings underscore the efficacy of the in-house ELISA as a viable serodiagnostic tool for AHS. Furthermore, the polyvalent antigen-based in-house indirect ELISA proved to be a reliable alternative for AHS monitoring, particularly in vaccinated horses, offering enhanced specificity. Additionally, this method is simpler, cheaper, faster, and more convenient than blocking ELISA and serum neutralization tests, making it a practical choice for routine AHS surveillance.